Memahami Karakteristik Guru Profesional - Della Puspita Sari; Amilya Nurul Erindha; Dr. H. Munawir M. Ag. (Pedir Research Institut, 2021)
In general the teacher can be interpreted as a person who has the responsibility to educate. In particular, the teacher can be defined as a person who is responsible for the development of students by seeking the development of all their potential, both affective, cognitive, and psychomotor potential. The word professional is related to a profession or requires special skills to run it. Teachers are born or exist since humans themselves exist, because once humans are born into the world, the actual educational process has occurred. Teachers are believed to be one of the dominant factors that determine the success of an education, therefore teachers must have characteristics as a professional. These characteristics include obeying laws and regulations, maintaining and improving professional organizations, maintaining relationships with colleagues, guiding students, obeying leaders, having a commitment to professionalism, and creating a good atmosphere in the workplace.